The profile of physical activity and coronary risk factors in Monica Jakarta survey (Medical Journal of Indonesia, 2001)
A population study was done to know the profile of daily physical activity including sports, and its influence on major coronary risk factors in three districts of Jakarta using questionnaire, physicaL and laboratory examination, and 12 leads ECC. The questionnaire gave the data about physical activity (work load and sport), and smoking habit. Work load was divided into light, moderate and heavy. Sport activity was divided into regular (≥ twice a week, 20 minutes or more), irregular (≤ once or occasional), and no sport activity. In addition, blood pressure (hypertension was grouped according to WHO criteria), total cholesterol (regarded as hypercholesterolemia when > 200 mg%), and ECG were measured. ECG interpretation was done using Minnesota Code. Statistical analysis was done using SPSS. Out of 2400 people there were 2073(86.4%) respondents that consist of 1086 females and 987 males. The profile of physical activity as a whole showed 33.4% light, 50.7% moderate and 15.8% heavy activity. OnLy 22.5% of respondents had sport regularly, while 30.3% had sport irregularly, and 47.2% had no sport activity. The type of sport was walking (45.0%), callisthenic (22.0%) jogging/running (15.6%), badminton (6.5%), volley ball/soccer (4.1%), tennis (3.8%), and golf (0.1%). There was a significant difference in the prevalence of hypertension between people with heavy (12.0%), moderate (44.8%) and light work load (43.2%) (P<0.003), in the prevalence of hypercholesterolemia (13.2%: 50.8%: 36%) (P<0.0003), and smoking (19.7%; 44.1%: 36.2%) (P<0.00001), respectively. The difference also occurred in the prevalence of abnormal ECG (Q/QS, ST and T abnormalities) between people having regular sport (19.0%), irregular (22.7%), and no sport activity (58.3% (P<0.05). The number of respondents having enough physical activity (including regular sport) was relatively low. Therefore, promotion should be done as a preventive method to overcome cardiovascular risk factors. (Med J Indones 2001; 10: 34-41) Keywords: Sport, ECG